Regional assessment of general education quality in Tomsk region; 2018 IEEE Global Engineering Education Conference - Emerging Trends and Challenges of Engineering Education - Mozgaleva P. I. Polina Igorevna; Zamyatina O. M. Oksana Mikhailovna; Mozgaleva A. I.; Costa Brito Cabral Pedro da (2018, 2018)
Title screen